PERAMALAN HARGA EMAS DUNIA DENGAN MODEL GLOSTEN-JAGANNATHAN-RUNCLE GENERALIZED AUTOREGRESSIVE CONDITIONAL HETEROSCEDASTICITY - Uswatun Hasanah; Agus Rusgiyono; Rukun Santoso (Jurnal Gaussian, 2022)
Gold investment is considered safer and has less risk than other types of investment. One of the important knowledge in investing in gold is predicting the price of gold in the future through modeling the price of gold in the past. The purpose of this study is to model the gold price in the past so that it can be used to predict gold prices in the future. The world gold price data is a time series data that has heteroscedasticity properties, so the time series model used to solve the heteroscedasticity problem is GARCH. This study has an asymmetric effect, so the asymmetric GARCH model is used, namely the Glosten-Jagannathan-Runkle GARCH (GJR-GARCH) model to model the world gold price data. The data is divided into in-sample data from January 3, 2012 to December 31, 2018 to create a world gold price model and out-sample data from January 1, 2019 to December 31, 2020, which is used to evaluate model performance based on MAPE values. The best model is the ARIMA(1,1,0) GJR-GARCH(1,1) model with a MAPE data out sample value of 18,93% which shows that the performance of the model has good forecasting abilities.